PARP-inhibitor treatment prevents hypertension induced cardiac remodeling by favorable modulation of heat shock proteins, Akt-1/GSK-3β and several PKC isoforms. - Laszlo Deres; Eva Bartha; Anita Palfi; Krisztian Eros; Adam Riba; Janos Lantos; Tamas Kalai; Kalman Hideg; Balazs Sumegi; Ferenc Gallyas; Kalman Toth; Robert Halmosi (PLoS ONE, 2014)
Spontaneously hypertensive rat (SHR) is a suitable model for studies of the complications of hypertension. It is known that activation of poly(ADP-ribose) polymerase enzyme (PARP) plays an important role in the development of postinfarction as well as long-term hypertension induced heart failure. In this study, we examined whether PARP-inhibitor (L-2286) treatment could prevent the development of hypertensive cardiopathy in SHRs. 6-week-old SHR animals were treated with L-2286 (SHR-L group) or placebo (SHR-C group) for 24 weeks. Wistar-Kyoto rats were used as aged-matched, normotensive controls (WKY group). Echocardiography was performed, brain-derived natriuretic peptide (BNP) activity and blood pressure were determined at the end of the study. We detected the extent of fibrotic areas. The amount of heat-shock proteins (Hsps) and the phosphorylation state of Akt-1(Ser473), glycogen synthase kinase (GSK)-3β(Ser9), forkhead transcription factor (FKHR)(Ser256), mitogen activated protein kinases (MAPKs), and protein kinase C (PKC) isoenzymes were monitored. The elevated blood pressure in SHRs was not influenced by PARP-inhibitor treatment. Systolic left ventricular function and BNP activity did not differ among the three groups. L-2286 treatment decreased the marked left ventricular (LV) hypertrophy which was developed in SHRs. Interstitial collagen deposition was also decreased by L-2286 treatment. The phosphorylation of extracellular signal-regulated kinase (ERK)1/2(Thr183-Tyr185), Akt-1(Ser473), GSK-3β(Ser9), FKHR(Ser256), and PKC ε(Ser729) and the level of Hsp90 were increased, while the activity of PKC α/βII(Thr638/641), ζ/λ(410/403) were mitigated by L-2286 administration. We could detect signs of LV hypertrophy without congestive heart failure in SHR groups. This alteration was prevented by PARP inhibition. Our results suggest that PARP-inhibitor treatment has protective effect already in the early stage of hypertensive myocardial remodeling.